2012
DOI: 10.1002/chem.201202825
|View full text |Cite
|
Sign up to set email alerts
|

On the Catalytic Mechanism of (S)‐2‐Hydroxypropylphosphonic Acid Epoxidase (HppE): A Hybrid DFT Study

Abstract: The mechanism of oxidative epoxidation catalyzed by HppE, which is the ultimate step in the biosynthesis of fosfomycin, was studied by using hybrid DFT quantum chemistry methods. An active site model used in the computations was based on the available crystal structure for the HppE-Fe(II)-(S)-HPP complex and it comprised first-shell ligands of iron as well as second-shell polar groups interacting with the substrates. The reaction energy profiles were constructed for three a priori plausible mechanisms proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 68 publications
3
30
0
Order By: Relevance
“…We found that the dioxygen molecule prefers to bind to the iron in a side‐on mode as suggested from the experiment . Most theoretical studies on the nonheme iron enzymes predicted a high spin septet ground state for the Fe−O 2 complex . Here too, the septet state with the side‐on conformation ( 7 1 side‐on in Figure A) was found to be the most stable one, and then was set as the reference point of 0 kcal mol −1 .…”
Section: Resultssupporting
confidence: 53%
“…We found that the dioxygen molecule prefers to bind to the iron in a side‐on mode as suggested from the experiment . Most theoretical studies on the nonheme iron enzymes predicted a high spin septet ground state for the Fe−O 2 complex . Here too, the septet state with the side‐on conformation ( 7 1 side‐on in Figure A) was found to be the most stable one, and then was set as the reference point of 0 kcal mol −1 .…”
Section: Resultssupporting
confidence: 53%
“…13,37 The same proton relay channel could use the newly formed water molecule to activate the ferryl oxygen through protonation in a similar manner as in these iron porphyrin model systems. More generally, ferryl protonation could play a significant role in the reactivity and selectivity of non-heme iron proteins such as the α-ketoglutarate-dependent halogenase SyrB2 38 and in ( S )-2-hydroxypropyl-phosphonic acid epoxidase (HppE), 39 which mediates the unusual epoxide formation in the biosynthesis of fosfomycin. In these cases, simultaneous ferryl protonation and substrate hydrogen abstraction could both facilitate C–H bond scission and disfavor hydroxylation of the incipient substrate radical.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is interesting to mention the QM-cluster study on the chemistry of hydroxypropylphosphonic acid epoxidase (HppE), where favorable binding of O2 to the iron center and reasonable barriers for substrate oxidation were obtained using DFT. [124] However, it transpired from later experiments that the enzyme is inactive with O2; it hardly even binds it, and it actually employs H2O2 as oxidant. [125] Answering why the QM-cluster calculations failed to detect the flaw in the assumptions would need a separate, higher-level study, but one can expect that the effects of the neglected or approximated environment may be quite significant for the step when O2 is transferred from aqueous solution through the protein cavities to the iron within the active site pocket, and may be less so for the inner-sphere chemistry occurring thereafter.…”
Section: Miscellaneous Monoiron Systemsmentioning
confidence: 99%